2004
DOI: 10.1002/ijc.20176
|View full text |Cite
|
Sign up to set email alerts
|

Increased adenoviral transduction efficacy in human laryngeal carcinoma cells resistant to cisplatin is associated with increased expression of integrin αvβ3 and coxsackie adenovirus receptor

Abstract: In our study, we investigated molecular mechanisms of increased adenoviral transduction efficacy in cisplatin-resistant human laryngeal carcinoma cells CA3 ST

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 36 publications
4
21
0
Order By: Relevance
“…However, this is very difficult to achieve experimentally due to the heterodimeric nature of integrins. Namely, the transfected β3 subunit could compete for available αv in a cell and decrease another αv heterodimer like αvβ5, as we described previously in a model of human laryngeal carcinoma cell line (Ambriović-Ristov et al, 2004).…”
Section: Discussionmentioning
confidence: 81%
“…However, this is very difficult to achieve experimentally due to the heterodimeric nature of integrins. Namely, the transfected β3 subunit could compete for available αv in a cell and decrease another αv heterodimer like αvβ5, as we described previously in a model of human laryngeal carcinoma cell line (Ambriović-Ristov et al, 2004).…”
Section: Discussionmentioning
confidence: 81%
“…Drug resistance is the major cause of unsuccessful chemotherapy, and our previously published data on HEp2-derived cisplatin resistant cell lines indicate that cisplatin resistant cells could be a better target for adenovirus gene therapy than the parental tumor cells because they could be infected more efficiently (Ambriović-Ristov et al 2004). We think that promoter activity is often neglected in analyzing the success of nonviral and viral therapeutic gene transfer for tumor therapy, especially in certain drug-resistant tumors that should, in the near future, be the first treated by gene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Drug-resistant human bladder cancer cells were shown to be more sensitive to adenovirus-mediated wild-type p53 gene therapy than drug-sensitive cells, but the mechanism was unclear (Shirakawa et al 2001). Our group has previously shown that the increased Ad5 transduction efficiency in a HEp2-derived cell clone resistant to cisplatin is due to the upregulation of the Ad5 receptors CAR and αvβ3 integrin (Ambriović-Ristov et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations